FOREIGN CULTURE ON THE CONSUMPTION HABITS AND LIFESTYLE OF THE MILLENIAL GENERATION: A CONCEPTUAL STUDY - Yuliniar (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2025)
The younger generation is essential in sorting and choosing what is good and what is bad in the fight to protect Indonesia's rich cultural legacy. However, the presence of other cultures frequently causes society—millennials in particular—to place a higher priority on individual liberty than on moral principles. Examining how other cultures affect millennials' lifestyles and spending patterns is the aim of this study. This study emphasises the significance of incorporating Pancasila values into national and state life as well as the need to preserve Indonesia's indigenous culture in order to screen out approaching foreign cultures. This study used a survey as its research approach. This study used a survey as its research approach. It is anticipated that society and the younger millennial generation will gain from this research by being more conscious of the value of protecting Indonesia's indigenous culture